Glacier thinning and adaptation assemblages in Nagar, northern Pakistan - Spies, Michael (ERDKUNDE, 2016)
This article draws on assemblage and actor-network theories to analyze local struggles of adaptation to glacier thinning in Nagar, a high mountain community in the central Karakoram of northern Pakistan. Framing adaptation as a process of assemblage-building of heterogeneous human and non-human actants, two village case studies are investigated where glacier thinning has dried up a source of irrigation water, turning cropland into desert. While in the first case case, villagers were able to construct a new and extraordinary water supply scheme with the help of external development agencies, in the second case, several approaches to utilize alternative water sources over three decades were unsuccessful. An account of the adaptation assemblages shows how a diversity of actants such as individual leaders, community, external agencies, construction materials, landslides and geomorphological features play variable and contingent roles in the success or failure of adaptation efforts, thus co-defining their outcome in complex ways. This article argues that a framing of adaptation as assemblage could offer an empirical and conceptually balanced perspective on adaptation that has the potential to account for the socio-natural complexities involved. While bearing some analytical challenges, it may provide an alternative to other understandings of adaptation to environmental and climate change by refraining from environmental reductionist theories, while avoiding to downplay the natural environment as a mere stage or object of sociopolitical struggles.